Environmental Impact on Seaweed Phenolic Production and Activity: An Important Step for Compound Exploitation - Lomartire, Silvia (2021)
Seaweeds are a potential source of bioactive compounds that are useful for biotechnological applications and can be employed in different industrial areas in order to replace synthetic compounds with components of natural origin. Diverse studies demonstrate that there is a solid ground for the exploitation of seaweed bioactive compounds in order to prevent illness and to ensure a better and healthier lifestyle. Among the bioactive algal molecules, phenolic compounds are produced as secondary metabolites with beneficial effects on plants, and also on human beings and animals, due to their inherent bioactive properties, which exert antioxidant, antiviral, and antimicrobial activities. The use of phenolic compounds in pharmaceutical, nutraceutical, cosmetics, and food industries may provide outcomes that could enhance human health. Through the production of healthy foods and natural drugs, bioactive compounds from seaweeds can help with the treatment of human diseases. This review aims to highlight the importance of phenolic compounds from seaweeds, the scope of their production in nature and the impact that these compounds can have on human and animal health through nutraceutical and pharmaceutical products.